Comparison of Proton Density Weighted Sequence with T2-Weighted Sequence to Detect Acute Osteoarthritis - Nasir, Faiza; Saeed, Iqra; Saleem, Zobia; Nasir, Muzna; Ayub, Namra (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Osteoarthritis is among the most common joint disorders globally. The application of MRI sequences leads to consistently improved diagnostic capabilities for early-stage osteoarthritis. Understanding the optimal sequence for accurate diagnosis is crucial for effective patient management. Aim: To evaluate the patients having acute osteoarthritis through the Proton Density (PD) weighting sequence of MRI and comparing it with the outcomes from the T2-weighted imaging. Methodology: This study employed comparative cross-sectional study design, utilizing the non-probability convenientsampling technique, and was conducted at a Service Hospital in Pakistan from August 2023 to December 2023. 59 patients having knee pain, inflammation, tenderness and joint stiffness were included and individuals having acute ligamentous injuries and instability were excluded Results: The study compared MRI findings of acute osteoarthritis using PDW and T2W sequences. Joint effusion was detected in 88.1% (PDW) vs. 86.4% (T2W). Meniscal tears were equally identified (72.8%), but PDW was more sensitive for cruciate (66.1% vs. 6.8%) and collateral ligament tears (38.9% vs. 8.5%). Both sequences detected bursitis equally (11.8%). T2W better identified osteophytes and bony spurs (59.3% each) compared to PDW (23.7% and 25.4%). Femoral and tibial condylar changes, subarticular cysts, synovial thickening, subchondral bone marrow changes, and subcutaneous edema were similarly detected by both sequences. Practical Implication: This allows for better imaging techniques, leading to improved patient care. The study’s results may prompt updates to clinical guidelines, recommending PDW sequences for early detection of osteoarthritis-related changes. Future research could focus on refining imaging techniques and developing new therapeutic approaches. Conclusion: Our study concludes that PDW sequences are superior in detecting early osteoarthritic changes, including ligament and meniscus tears, cartilage defects, and bone edema, compared to T2W sequences. This highlights PDW’s potential in enhancing early diagnosis and prognosis of acute osteoarthritis.